汉语与印尼语构词词缀（构成名词）对比分析 - Noni, Nur Nasharuddin; Samad, Ita Sarmita; Wahyuni, Sry; As’ary, Muawwal Al (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2025)
Affixes are linguistic units of derivational morphology in Chinese and Indonesian. In bothlanguages, the affix is attached to the root morpheme as an additional morpheme to produce a newword. The phenomenon of affixation in both languages is unique and worth studying. This paper ismeant to make it relatively easy for students to learn Chinese and Indonesian affixal derivationalword formation. This study adopts the literature research method to analyse the grammatical meaningand affixation forms of constituent nouns in both languages. Similarities were found in both Chineseand Indonesian, where root morphemes can be combined with different affixes (morphemes) fordifferent word classes to produce new words. The affixes used to form new words in Chinese aremuch less abundant than in Indonesian, and the differences between the two languages can be seenin the number of affixes, the corresponding word formation results, and the grammatical meanings.The study of these affix differences can identify patterns, deepen the understanding of learningbetween Chinese and Indonesian, improve the quality of translation between Chinese and Indonesian,and hopefully contribute to the learning and teaching of Chinese and Indonesian.Keywords: Chinese and Indonesian; affixes; comparative analysis